Modeling and performance analysis of high-efficiency thermally-localized multistage solar stills. (15th May 2020) - Zhang, Lenan; Xu, Zhenyuan; Bhatia, Bikram; Li, Bangjun; Zhao, Lin; Wang, Evelyn N.
Highlights: Modeling framework of thermally-localized multistage solar stills (TMSS) is developed. Heat and mass transfer in the TMSS are analyzed in detail. Optimization strategies for the TMSS are presented. Ultrahigh solar-thermal cumulative efficiency over 700% is predicted. Abstract: Seawater desalination is a promising solution to global water shortage. Commercially available desalination technologies typically require large installations which can be impractical for developing regions without well-developed infrastructure. Passive solar desalination promises a viable solution, but can suffer from low efficiencies. Recent advances in the thermal design of small-scale solar desalination systems have demonstrated the potential for high-efficiency solar desalination in portable systems. In particular, the concept of a thermally-localized multistage solar still (TMSS) – which combines localized heating of a capillary flow with condensation heat recycling – has been experimentally demonstrated very recently and achieved over 100% solar-thermal cumulative efficiency. However, a fundamental understanding of the heat and mass transfer, efficiency limits and optimization strategies are missing in the literature. This work presents a modeling framework that evaluates the thermal and vapor transport in a model TMSS system with varying device configuration and predicts its solar desalination efficiency. We demonstrate that an ultrahigh solar-thermal cumulative efficiency, many times higher than that of conventional solar stills, can be achieved by optimizing the number of stages and device geometry. Specifically, our modeling shows that the efficiency of the capillary fed TMSS is limited by the dissipation of thermal energy to the environment during condensation and significant gains in efficiency can be achieved by minimizing this loss. This work provides insights into physical processes critical for thermally-localized portable solar distillation which could lead to high-performance desalination or water purification technologies.